ETIKA LITERASI INFORMASI MASYARAKAT MUSLIM DALAM PERSPEKTIF AKSIOLOGI FILSAFAT ILMU - Jumaini Jumaini; Muhaemin Latif Muhaemin Latif; Mubarak Taswin Mubarak Taswin (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The rapid development of information and communication technology has transformed the way people access, manage, and disseminate information. This study aims to analyze the ethics of information literacy among Muslim communities from the perspective of the axiology of the philosophy of science. The research employs a descriptive qualitative approach with data collected through open-ended questionnaires distributed to six respondents from diverse professional backgrounds, including civil servants, teachers, and students. Data were analyzed using thematic analysis and content analysis, and validity was ensured through theoretical triangulation by comparing respondents’ answers with concepts from the philosophy of science, information ethics, and Islamic thought. The findings indicate that the axiology of the philosophy of science emphasizes the value and beneficial use of knowledge as essential aspects of information utilization. Information literacy is not merely concerned with technical skills in accessing and evaluating information but also with ethical awareness in using information responsibly. From an Islamic perspective, the ethics of information literacy are reflected in the practice of verifying information sources, maintaining honesty in conveying information, respecting the rights and privacy of others, and utilizing information for the common good. Therefore, strengthening information literacy ethics based on Islamic values and the axiology of the philosophy of science is a strategic necessity for fostering a critical, wise, and responsible Muslim society in the digital era.